Land-use land cover changes and their relationship with population and climate in Western Uganda - Kishaija, Noel; Adam, Abdelbagi Y F; Heil , Bálint (Journal of Degraded and Mining Lands Management, 2024)
Sustainable management of land and its ecosystem requires well-documented Land-use and Land Cover changes (LULCCs) that have occurred over time. The objective of this study was to document the LULCCs, determine their relationship with climate and population changes in Western Uganda, and provide evidence to support decision-making in this region. This study utilized satellite images for the years 1992, 2000, 2010, and 2020 obtained from the European Space Agency Climate Change Initiative (ESA CCI), Climatic data from NASA, and Population Data from the Uganda Bureau of Statistics (UBoS). LULCCs and their influencers were characterized in the region, for the period 1992 to 2020. ArcGIS Pro Software Program was used to Filter time series data using Definition Query, while the scatterplot was employed to determine the relationship between changes in climate and population on LULCCs. Results indicate that LULC is dominated by agriculture, covering (66.46%), followed by forests (16.22%), waterbodies (8.0%), grassland, shrubland, wetland, and urban areas at (6.11%), (2.63%), (0.49%) and (0.1%) respectively. From 1992 to 2020, the area under agriculture, forest and urban increased by 0.1%, 0.1%, and 0.08%, respectively, while Grassland, wetland, and shrubland declined by (0.22%), (0.05%), and (0.01%) respectively. LULCCs for areas under wetland, grassland, and urban areas have a stronger relationship with precipitation and population growth. This information can be used by the decision-makers at the local, district, and national levels to better guide land-use practices aimed at sustainable land-use management for the current and future generations.